2021
DOI: 10.37637/ab.v4i3.745
|View full text |Cite
|
Sign up to set email alerts
|

Kelimpahan Fauna Tanah pada Ekosistem Pascabakar Kecamatan Mentebah, Kabupaten Kapuas Hulu, Kalimantan Barat, Indonesia

Abstract: Sistem pengelolaan hutan di Kabupaten Kapuas Hulu selama ini kurang optimal sehingga luas hutan dari tahun ke tahun mengalami penurunan yang mengakibatkan kualitas hutan semakin menurun. Eksploitasi hutan seperti penebangan hutan, peningkatan peralihan fungsi kawasan hutan menjadi pemukiman, perkebunan, perladangan berpindah, dan terjadinya kebakaran hutan merupakan ancaman yang serius terhadap ekosistem hutan terutama keberadaan fauna tanah dan hilangnya keanekaragaman hayati. Fauna tanah merupakan bagian dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The presence of soil fauna is influenced by various factors. The abundance of soil fauna is affected by climatic factors such as rainfall, temperature, humidity, and soil factors such as aeration, soil temperature, litter, soil moisture, acidity, nutrient content, as well as vegetation cover factors such as forests, grasslands, shrubs, and agriculture [20]. LSD test, which was presented on Tabel 1 showed that soil fauna abundance was significantly different in every elevation (altitude) at the 95% confidence level.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of soil fauna is influenced by various factors. The abundance of soil fauna is affected by climatic factors such as rainfall, temperature, humidity, and soil factors such as aeration, soil temperature, litter, soil moisture, acidity, nutrient content, as well as vegetation cover factors such as forests, grasslands, shrubs, and agriculture [20]. LSD test, which was presented on Tabel 1 showed that soil fauna abundance was significantly different in every elevation (altitude) at the 95% confidence level.…”
Section: Resultsmentioning
confidence: 99%